Pengelolaan Supervisi Manajerial Pengawas DiDabin 7 Uptd Pendidikan Kecamatan Purwodadi - Kustiyani, Kustiyani, Prof. Dr. Sutama, M.Pd, Dr.Suyatmini,SE.,M.Si (2016)
Implementation of managerial supervision of school inspectors hearts Frame assist the head of the school in order to improve the effectiveness quality And Delivery of Education and Learning . Managerial supervision focuses on observation on aspect - aspect Management and Administration School serves as Support ( support ) the implementation of Learning . The purpose of research is to describe the planning , implementation , feedback managerial supervision supervisor in Dabin 7 UPTD District of Purwodadi . This type of research used in this research is qualitative research . This study design ethnography thorough explanation of the complexity of the group 's life . Data collection techniques using triangulation which is a combination of observation , documentation and interview . Data analysis was performed with this model of data collection , data reduction , data display , and conclusion. The validity of the data required inspection techniques based on the degree of confidence , keteralian , dependability and certainty The results of this study were (1) Planning managerial supervision consisting of (a) Schedule managerial supervision (b) managerial supervision Instrument (c) The list of schools to be supervised. (2) Implementation of managerial supervision is carried out through three stages: the initial activity is to explain the intent and purpose of arrival at the school superintendent, explained the format of the principal performance assessment and performance assessment scenarios agreed school.On head supervisor assessing the performance of the core activities of the Principal. ie relating to aspects of the management and administration of the School with the steps that have been agreed at once record things that are less corresponding. On activities cover supervisor explained to the headmaster about the results of the assessment. supervisor explained the result by showing the performance of the principal aspects of strength and weakness. (3) Feedback supervision manajerial. to correct the findings discrepancies or problems found . Implementation of managerial supervision by supervisors in Dabin 7 UPTD District of Purwodadi there are 3 stages: planning , implementation and feedback in order to improve the quality and effectiveness of education. Keywords : managerial , school inspectors, supervision